Islanders in the empire : Filipino and Puerto Rican laborers in Hawai'i - Poblete, JoAnna, 1974- (Asian American experience., 2014)
"In the early 1900s, workers from new U.S. colonies in the Philippines and Puerto Rico held unusual legal status. Denied citizenship, they nonetheless had the right to move freely in and out of U.S. jurisdiction. As a result, Filipinos and Puerto Ricans could seek jobs in the United States and its territories despite the anti-immigration policies in place at the time. JoAnna Poblete's Islanders in the Empire: Filipino and Puerto Rican Laborers in Hawai'i takes an in-depth look at how the two groups fared in a third new colony, Hawai'i. Using plantation documents, missionary records, government documents, and oral histories, Poblete analyzes how the workers interacted with Hawaiian government structures and businesses, how U.S. policies for colonial workers differed from those for citizens or foreigners, and how policies aided corporate and imperial interests. A rare tandem study of two groups at work on foreign soil, Islanders in the Empire offers a new perspective on American imperialism and labor issues of the era"--